2013
DOI: 10.5301/jva.5000160
|View full text |Cite
|
Sign up to set email alerts
|

Central Vascular Catheters versus Peripherally Inserted Central Catheters in Nurse Anesthesia. A Perspective within the Greek Health System

Abstract: PICCs under ultrasound guidance constitute the solution of choice for patients and they definitely surpass the CVCs focusing mainly on the improvement of the quality of life and the satisfaction of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Across several studies, pain during catheter insertion was reported in 0% to 18% of patients using PICCs. [11][12][13][14][15] In the study by Konstantinou et al, 11 no significant difference was reported for pain during the procedure between PICCs and CICCs (7.7% vs. 12.2%, P = 0.502). In the study by Pedersen et al, 14 8.7% of patients with PICCs experienced pain during insertion, compared to 23.4% of patients with PIVC lines.…”
Section: Efficacy Outcomesmentioning
confidence: 88%
See 4 more Smart Citations
“…Across several studies, pain during catheter insertion was reported in 0% to 18% of patients using PICCs. [11][12][13][14][15] In the study by Konstantinou et al, 11 no significant difference was reported for pain during the procedure between PICCs and CICCs (7.7% vs. 12.2%, P = 0.502). In the study by Pedersen et al, 14 8.7% of patients with PICCs experienced pain during insertion, compared to 23.4% of patients with PIVC lines.…”
Section: Efficacy Outcomesmentioning
confidence: 88%
“…The study by Konstantinou et al 11 reported no significant difference between PICCs and CICCs (P = 0.18) in the number of venipunctures required for successful catheter insertion. However, fewer venipunctures were required with PICCs ver-sus PIVCs in the study by Periard at al 10 for initial catheter insertion (1.16 vs. 2.27, P < 0.01).…”
Section: Efficacy Outcomesmentioning
confidence: 92%
See 3 more Smart Citations